Rancang Bangun Smart Box untuk Keamanan Penerimaan Paket - Shadrina Arifah; Nina Paramytha (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
In the digital era, online buying and selling transactions are increasing, so that shipping services have an important role. However, there are various problems in package delivery, such as loss or damage due to the absence of the recipient at the location. This study aims to design and build an IoT-based Smart Box that allows safe package receipt. This system is equipped with a keypad, ultrasonic sensor, load cell sensor, and ESP32-CAM for automatic image capture and sending notifications to users via Telegram. Tests were carried out on various aspects of the system, including sensors, IoT connectivity, and package storage security. The test results show that the tool can function well in securing packages and providing real-time notifications to recipients.